A comprehensive review on the diagnosis and management of intimal sarcoma of the pulmonary artery. (March 2020) - Assi, Tarek; Kattan, Joseph; Rassy, Elie; Moussa, Tania; Nassereddine, Hussein; Honore, Charles; Adam, Julien; Terrier, Philippe; Dumont, Sarah; Mir, Olivier; Le Cesne, Axel
Highlights: Intimal sarcomas affect great vessels and the heart, commonly the pulmonary artery. MDM2 and PDGFRA amplifications confirm the histopathological diagnosis. Early aggressive surgery with complete resection and clear margins is standard. Doxorubicin-based chemotherapy remains the most effective strategy in advanced STS. Abstract: Only a few hundred cases of intimal sarcomas of pulmonary artery (ISPA) were reported on the literature. Diagnosis of this rare entity is a challenging dilemma with the need for a high expertise in the radiological and pathological identification of ISPA. Treatment strategies rely initially on an early aggressive surgery aiming for complete surgical resection with clear margins while no clear recommendations guiding the choice for additional drug therapy or radiotherapy exist. In this article, we perform an extensive review of the literature on ISPA with details on the clinical presentation, diagnosis and management strategies. An additional goal of this paper is to make practicing oncologists aware of this rare entity with clear idea on the initial management.